Figure in movimento: José Saramago e il personaggio come rifigurazione (ENTHYMEMA, 2020)
The present analysis focuses on concepts and characters in the work of José Saramago, in direct correlation with the ongoing reflection that, within the theoretical context of narrative studies, has been the object of study of the research project Figures of Fiction. Taking into account the breadth of media studies and also the so-called afterlife of some of Saramago's literary characters, I consider the movement of these figures and I develop the dynamic aspect of representation that is implicitly portrayed, drawing from the notion of “re-figuration”. Based on this concept, I show how fictional characters are figures that travel from the literary text to our world and here continue to reside with us.